Semi-empirical Calculation for the Electronic Structure of Schiff Base - Tondon, H.C. (Asian Journal of Chemistry, 2010)
Ninhydrin is a triketo compound which is stable in hydrated form and is used in the detection and estimation of amino acids. It reacts with amino acids producing purple coloured Schiff base. Experimental data are available for this compound, so it prompted us to study the electronic structure of the reaction with substituted amines, by using quantum mechanical calculations. The theoretical study reveals that the para position of amines makes ninhydrin a high-potential ligand , when they react with each other.